Building Rights Over Management Rights In The Batam Free Trade Area: Perspectives On Certainty And Legal Protection - Setiawan, Anjas; Helmi, Helmi; Rosmidah, Rosmidah (Ipso Jure, 2026)
Hak Guna Bangunan (HGB) above the right of Management (HPL) is a form of state land utilization that develops in the practice of managing national strategic areas, especially in the Free Trade Area and free port of Batam. However, this practice raises complex juridical issues, especially with regard to the vagueness of the legal status of HPL which is not explicitly regulated in the agrarian Basic Law, resulting in weak certainty and legal protection for HGB holders. This study aims to analyze the legal status of HGB above HPL in the land management system in Batam, assess the application of the principles of Indonesian land law in the regulation and management by the Batam Enterprise Board, and formulate reformulation of HGB settings above HPL in order to ensure the protection of the rights of related parties. The research method used is normative legal research with a statutory, conceptual, and systemic approach, which is analyzed qualitatively with prescriptive reasoning. The results showed that HGB regulation above HPL is still characterized by emptiness and disharmony of norms, dominance of administrative authority of area managers, and not optimal application of the principles of legal certainty, justice, and rights protection. This study concludes that the reformulation of HGB arrangements above HPL is needed through the affirmation of the position of HPL as a state Public Authority, strengthening the status of HGB as a right to legally protected land, as well as the arrangement of Area Management Authority to be in line with the principles of National Land Law and state law.